Therapeutic Ethics: Managing Anger, Negative Thoughts and Depression According to al-Balkhī - Abdullah, Fatimah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2011)
Proper control and transformation of the human self or soul is essential for psycho-spiritual health. On the contrary, absence of control of the self and transformation results in psycho-spiritual imbalance. When the soul is healthy, all its faculties will be free from negative psychological symptomic behaviour such as anger, panic, depression and the like. To promote the wellbeing of the soul, we need to manage our emotions. For, spiritual joy and happiness are basic states on which the health of the soul can be gauged. Thus, in order to properly sustain our soul, we should shield it from emotional and spiritual pathological habits and seek to root it in joyfulness conceived of as a spiritual state and not a skin-deep emotion. Islamic literature provides various and integrated approaches in managing emotions. Material on this issue can be found in Islamic traditions regarding the Prophet and his companions as well as in the contributions of Muslim scholars throughout the centuries. Islam as a way of life and a worldview offers its followers insights to treat the malaise of the soul in holistic, cognitive, rational and psycho-physiological ways. For instance, spiritual cognitive therapy can have a significant impact on the treatment of emotional and spiritual disorders. This article attempts to highlight the contributions of one of the great Muslim scholars, namely Abu Zayd Ahmed Ibn Sahl al-Balkhī (d. 322 AH), in treating the sickness of the soul as revealed by psychological symptoms such as anger, negative thoughts and depression as well as in managing psychological imbalance.